The impact of the two-year COVID-19 pandemic on hospital admission and readmissions of children and adolescents because of mental health problems - Raffagnato, Alessia; Miscioscia, Marina; Bruni, Gaia; Del Col, Lara; Traverso, Annalisa; Ferrarese, Martina; Ancora, Caterina; Zanato, Silvia; Gatta, Michela (Frontiers in Public Health, 2023)
Purpose: This paper aimed to investigate the specific risk factors and psycho-social–clinical features of hospitalized neuropsychiatric patients during the COVID pandemic years and to analyze the hospital readmission phenomenon, which, according to recent studies, increased in frequency during the first pandemic period. Patients and methods: This is an observational retrospective cohort study on 375 patients from 0 to 17 years hospitalized between 1 February 2018 and 31 March 2022 due to neuropsychiatric problems. Female patients were prevalent: there were 265 females versus 110 males (M= 13,9 y; SD 2,30 y). The total sample was divided into two groups: the pre-COVID-19 group (160 inpatients hospitalized between February 2018 and February 2020), and the COVID-19 group (215 inpatients hospitalized between March 2020 and March 2022). In order to deepen the readmission phenomenon (second aim), we selected from the two groups patients with at least one hospital readmission within 365 days after the first discharge. Multiple variables (socio-demographic, clinical, psychological, and related to hospitalization) were collected for each patient through the review of medical materials. Results: The risk factors for mental health disorders were similar between the two groups, except for the significantly increased use of electronic devices in the COVID-19 group going from the 8.8% in pre-COVID-19 to 29.2% . Patients suffering from eating disorders increase from 11.3% to 23.8%. Hospital readmissions almost increase from 16.7% in the pre-COVID-19 two-year period to 26.2% the COVID-19 period. A total of 75% of patients hospitalized three or more times in the last two years and 85.7% of the so called “revolving door “patients (with relapse within three months after discharge) were identified in the COVID-19 group. However, the comparison between the two groups of patients readmitted before and during the COVID-19 pandemic did not show any differences in terms of socio-demographic and clinical characteristics. Conclusion: In conclusion, there was a significant increase in hospital readmissions, but these results suggest the need for better coordination between hospital and territorial services in managing the complexity of mental health problems related to COVID-19 pandemic situations and the necessity to implement prevention strategies and services.